O ensino de oncologia em enfermagem: um panorama do Brasil, Estados Unidos e outros países - Medeiros, Amanda Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The incidence of neoplasias has increased worldwide every year, and the training of qualified nurses for quality care provision to oncologic patients is necessary. This study aimed at identifying, in the literature, how oncology has been taught in the curricula of several undergraduate nursing programs in Brazil, the United States and other countries. The articles were located on Internet-based databases, namwly Lilacs and Scopus, from which 35 publications were found, and 18 articles were included. In Brazil, oncology is taught in undergraduate nursing programs in an isolated and punctual fashion, and it is not included in curricula. Parallelly, in the other countries included in the study, similarity was found as to this aspect; however, there is evidence of the implantation of elective and extracurricular courses. It is noteworthy that, in Brazil, there is evidence of government policies for oncology teaching and cancer control; nevertheless, such guidelines have not been concretized in curricula. The study showed a scenario in which oncology teaching in undergraduate nursing programs is insufficient or inexistent both in Brazil and in other countries, which compromises the training of future qualified professionals that will be attentive to that theme, since cancer is a frequent pathology, and the presence of nurses is fundamental for the care of such patients from diagnosis to cure, or even during occasional death

A incidência das neoplasias vem aumentando a cada ano em todo o mundo, e faz-se necessária a formação de enfermeiros capacitados a prestar assistência de qualidade ao paciente oncológico. O presente estudo objetivou identificar na literatura como o ensino de oncologia tem se dado no currículo dos cursos de graduação em enfermagem do Brasil, Estados Unidos e outros países. Os artigos foram localizados nas bases de dados da internet Lilacs e Scopus, de onde foram levantadas 51 publicações, das quais 18 artigos foram incluídos. No Brasil, o ensino de oncologia na graduação de enfermagem se dá de maneira isolada, pontual, e não inserido na grade curricular; paralelamente, nos demais países da pesquisa há evidências da implantação de disciplinas eletivas e cursos extra-curriculares. Vale ressaltar que no Brasil há evidências da política governamental de ensino da oncologia e controle do câncer, no entanto essa diretriz não se concretiza na prática das grades curriculares. O estudo evidenciou um panorama em que o ensino de oncologia na graduação de enfermagem é insuficiente ou inexistente tanto no Brasil como em outros países, o que compromete a formação de futuros profissionais qualificados e despertos para a temática, uma vez que o câncer é uma patologia freqüente e que a presença do enfermeiro é fundamental no cuidado dessas pessoas, desde o diagnóstico e a cura ou até a eventual morte
Keywords: Enfermagem; Oncologia; Ensino